The Role of Regional Organizations in East Asian Regional Cooperation and Intergration in the Field of Higher Education - Nguyen, Thuy Anh (H. : ĐHKT, 2016)
This paper analyzes the role of regional higher education organizations in promoting cooperation and integration in the fi eld of education in East Asia. More specifi cally, this paper examines whether there are differences in the approaches that these organizations are taking in comparison with other regions and discusses the implications of this study's findings.